Exploring ethnopedology in the Ecuadorian Andean highlands: A local farmer perspective of soil indicators and management - Jiménez, Leticia; Jiménez, Wilmer; Ayala, Nataly; Quichimbo, Pablo; Fierro, Natacha; Capa-Mora, Daniel (Geoderma Regional, 2024)
The aim of this study was to investigate the management practices and productive soil indicators as perceived by smallholder farmers in the highlands of Ecuador. By doing so, we sought to gain a better understanding of soil fertility in this area and compare it to know physical-chemical soil parameters. To achieve this goal, we conducted 555 semi-structured surveys with farmers in the Ecuadorian highlands. These survey results were then compared with data relating to carbon, texture, and soil pH values obtained from the GEOPORTAL platform of the Ministerio de Agricultura y Ganadería (scale 1:25000), the information was collected since 2018 by the authors. Our results indicate that farmers have a reasonable understanding of soil fertility and the main factors that affect it. In response to pollution problems, farmers have developed local strategies to aid in soil conservation and improve fertility. Furthermore, most of the knowledge that farmers possess about soil fertility has been gained from their relatives. Based on our results, we conclude that linking local soil knowledge with scientific knowledge will contribute to a more comprehensive understanding of soil fertility, being more relevant for small farmers texture, color, deep, stoniness and workability. This will be important for developing effective management practices that can help to sustain soil fertility in the Ecuadorian Andean Highlands.